Institutional Arrangements of Business Process Digitalization in Public Administration: The Case of Ukraine - Jaroslaw SZREDER; Iuliia PADAFET (Communications of International Proceedings, 2022)
Many research has been conducted in Western, democratic and developed societies, with very little known about business process digitalization in public administration  in less developed countries. This article investigates how business process digitalization affect institutional dimensions in Ukraine. It was identified most critical factor in favor of the creation of new institutional arrangements of business process digitalization The current technological structure and level of development of information and communication technologies will solve this important task and integrate all information components of the country's socio-economic spheres into a single complex.
Keywords: Digital transformation; Digitization; Digital government; Digital technologies.